To the opening of the Perinatal Center at the City Clinical Hospital № 67 - N. A. Makatsariya (Акушерство, гинекология и репродукция)
Here, the history оf Maternity Hospital at the City Clinical Hospital № 67 as well as the history of the Department of Obstetrics and Gynecology, Filatov Clinical Institute of Children's Health of Sechenov University are discussed.